Simulation of an Industrial Packed Column for Reactive Absorption of CO2 - Gómez, C. (2003)
The steady-state simulation of a reactive absorption column is presented. The absorber is used in a large-scale ammonia plant to remove CO2 from the process gas stream. To enhance the absorption process, high pressures and low temperatures are commonly used (T = 45-80 °C, P = 30-40 bar). At the outlet of the absorber, the CO2 content in the process gas must be reduced to less than 500 ppm (dry basis) to avoid an excessive temperature rise in the methanation reactor (downstream of the absorption section). To represent the gas-liquid system, a rigorous mathematical model based on the two-film theory is considered. The heat effects are taken into account. The behaviour of different process variables for a reference operating condition is analyzed. The influence of changes in some operating variables is evaluated.